Sustainable Energy Technology (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Topic "Sustainable Energy Technology" covers a number of papers concerning sustainable energy technologies such as floating tidal current power stations, solar-powered thermoelectric-based cooling and heating systems, life cycle assessment of merging recycling methods for spent lithium-ion batteries, organic Rankine cycle system review, offshore floating wind turbine, biomass integrated air gasification regenerative gas turbine power plants, etc. Therefore, studies of advanced techniques and methods in sustainable energy technology are included. This Topic also includes a comprehensive overview and in-depth technical research papers that address the recent progress in sustainable energy technology. It also provides cutting-edge research in sustainable energy technology development. Overall, this Topic is conducive to researchers, advanced students, technical consultants, and decision-makers in industries and politics for learning advances in energy development trends.